Digest: Evolution of eusociality favored by split sex ratios under worker‐control. (10th December 2019) - Ernst, Ulrich R.
Abstract: Eusociality has repeatedly independently evolved in ants, bees, and wasps (Hymenoptera), leading to the idea that haplodiploidy may be an important driving factor in this group. Using a modeling approach, Quiñones et al. show that split sex ratios and worker control of sex ratios (achieved by removal of male brood) can promote the initial evolution of helping raise offspring of related individuals. However, over time, these factors can result in social polymorphism, that is, a mix of solitary and social nests, or to eusocial colonies with three different strategies, namely those that produce mostly females, mostly males, or a balanced sex ratio.